ANALISIS PENGARUH PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI JAWA TIMUR: Analysis of Education and Health Effects on the Human Development Index in East Java Province - Helen Aulia Nugroho; Nurul Lathifah (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of education and health on the Human Development Index (HDI) in East Java Province during the period 2020–2024. The problem addressed in this research is the disparity of HDI achievements across regions, particularly between the mainland and Madura Island, which reflects unequal access to education and health services. The research method employed was quantitative with panel data regression using a natural logarithm transformation, estimated through IBM SPSS 25. The findings reveal that education has a positive and significant effect on HDI, confirming its fundamental role in improving human development, while health, measured through health complaints, shows a positive but insignificant effect. Simultaneously, education and health together explain 50.4% of HDI variation, with the remaining 49.6% influenced by other factors not included in the model. These results suggest that strengthening access and quality of education should be prioritized to accelerate HDI improvement, while health indicators require further refinement to better capture the real condition of society.